Contemporary Issues in Finance : Current Challenges from Across Europe. - Grima, Simon; Bezzina, Frank; Romanova, Inna.; Rupeika-Apoga, Ramona (Bingley : Emerald Group Publishing Limited, 2016)
Includes studies on different topical issues in finance by the participants of the 8th international scientific conference "New Challenges of Economic and Business Development - 2016" this new work contains research from various European countries, specifically Germany, Italy, Latvia, Malta, and Poland.
IntroductionTheoretical Aspects of Motivation for Mergers and Acquisitions; The Goal of Mergers and Acquisitions -- An Increase in Firm Value; Firms' Mergers and Acquisitions: European Example; Mergers and Acquisitions in Latvian Dairy Industry; Conclusions; References; Critical Factors of Pre-Acquisition Due Diligence in Cross-Border Acquisitions; Introduction; Critical Factors of Pre-Acquisition Due Diligence; Results of the Quantitative Research and Discussion; Conclusions and Suggestions; References; Business Consulting Studies; The FDI Inflow to Special Economic Zones in Poland.
Print version record.
ReferencesBanking and Fintech: A Challenge or Opportunity?; Introduction; Recent Trends in FinTech; FinTech and Banks: Competitors or Partners?; The Main Risks Related to Development of FinTech; Conclusions; Note; References; Analysis of Crowdfunding in European Union: Performance and Perspectives; Introduction; Research Results and Discussion; Understanding the Concept of Crowdfunding; Entrepreneurship in the EU: Role and Profile of the SMEs; Crowdfunding Fitness to Support Entrepreneurship in the EU; Conclusions, Proposals, Recommendations; References.
Introduction.
Added to collection customer.56279.3
Keywords: Finance -- Europe; Finances -- Europe; Finance; Banking; BUSINESS & ECONOMICS -- Finance; Finance; Europe